To a question on crisis of social hygiene and evolution of concept of public health services - I. V. Vasilyev; A. V. Kalinichenko (Бюллетень сибирской медицины, 2008)
Change of political and economic conditions should change a subject and methods of social study essentially. In postreorganization Russia the purposes of the state, methods and forms of the government, a subject and methods of a science have changed «Social hygiene» Were transformed unsystematically and till today's time are not certain. This circumstance has caused crisis of social hygiene as sciences. It is necessary to define a subject and methods of a science «Public health and public health services» on the basis of the right.